Implementasi Program E-Retribusi Pasar Batusangkar dalam Meningkatkan Pendapatan Asli Daerah Kabupaten Tanah Datar - Difa Zalsyabilla; Jumiati Jumiati (PUBLICNESS: Journal of Public Administration studies, 2022)
This study aims to describe the implementation of the Batusangkar Market Levy E Program in Increasing Local Revenue (PAD) of Tanah Datar Regency and to identify the factors that influence the implementation of the Batusangkar Market E-Retribution Program. The type of research used in this research is descriptive qualitative research, namely the data collected in the form of words, pictures, and not numbers. Implementation of the Batusangkar Market E-Retribution Program in Increasing Local Revenue (PAD) of Tanah Datar Regency, adjusting to the George C. Edward III implementation model, among them: Communication, Resources, Disposition and Organizational Structure. Based on the results of research conducted by researchers regarding the Implementation of the E-Retribution Program in Batusangkar Market in Increasing Local Revenue (PAD) of Tanah Datar Regency, the authors can draw the conclusion that the implementation of the e-retribution program at the Batusangkar Market has been implemented, but in its implementation it has not been optimally appropriate. with the factors that affect the implementation of policies or programs according to George C. Edward III.